Reducing turnover intention effective employee retention strategies for millennials in regional offices of national government agencies in Eastern Visayas - Almendra, Danna Kristina Z.; Baylon, Gwyneth G.; Capili, Dyanne Dane D.; Miflores, Stenelie Renie A.
The millennials are greatly associated with the term "job-hoppers" which could be attributed to their upbringing and the technological advances emerging throughout their life. Due to these changes, they have a different set of priorities and expectations from other generations. This mixed-method study aims to investigate the millennials expectations in the workplace, as well as their experiences and its alignment between the standardized retention policies implemented by the Civil Service Commission (CSC), utilizing Herzberg's Two-Factor Theory as a framework. Data was collected from 17 National Government Agencies in Tacloban City and Palo, Leyte, focusing on millennials born between 1988 and 1996, holding plantilla positions, and with at least two years of experience. There were 137 survey respondents and 25 interview participants. Millennial expectations in the workplace implementation of policies are revealed through the quantitative phase. With regards to motivation, millennials highly value advancement, personal growth, and the work itself, with the least regard for recognition, achievement, and responsibility. Hygiene factors revealed high expectations for job security, working conditions, and personal life, while the bottom factors include status, salary, and personal life. Gaps were identified through the analysis of the qualitative data and along with the review of the adequacy of the standardized retention policies on millennial turnover intentions. It revealed inconsistencies in achievement, recognition, interpersonal relations, supervisor quality, company policy and administration, working conditions, and personal life. The study provides recommendations for action on how public offices can reduce turnover intentions among millennials and recommendations for further research. Applying such recommendations could help enhance the policy-making processes in the public sector to address millennials' needs and turnover intentions.